Mean field and beyond mean field calculations of hypernuclei for study of electroproduction - Veselý P.; De Gregorio G.; Knapp F.; Petrellis D.; Bydžovský P.; Denisova D.; Pokorný J.; Skoupil D.; Lo Iudice N. (EPJ Web of Conferences, 2022)
We present two methods, the Nucleon-Lambda Tamm Dancoff Approximation (NΛ TDA) and the Equation of Motion Phonon Method (EMPM) suitable for calculating hypernuclear energy spectra and structure. These methods are applicable for hypernuclei of wide range of masses with one Λ particle replacing one nucleon in an even-even nuclear cores. Using an effective Lambda-nucleon (ΛN) potential both methods were applied to calculate the energy spectrum of 12ΛB and also one body density matrix elements (OBDME). The OBDME were applied to calculate the electroproduction cross section of 12ΛB. We obtained better agreement with the experimental data by using EMPM than NΛ TDA. We plan to provide theoretical prediction (by applying the same methods and ΛN potentials) of the cross section in electroproduction of 40ΛK and 48ΛK.